The atlas of endangered species - Mackay, Richard (Berkeley : University of California Press, 2009)
Vividly illustrated with full-color maps and detailed graphics, The Atlas of Endangered Species catalogs the inhabitants of a wide variety of ecosystems, including forests, mangroves, and coral reefs. It examines the major threats to biodiversity, from loss of habitat to hunting, and describes the steps being taken toward conservation.
Extinction is forever -- Ecosystems -- Fragile regions -- Endangered animals and plants -- Endangered birds -- Issues of conservation -- World tables.
"A Myriad edition"--P. [4] of cover.
Includes bibliographical references (p. 122-125) and index.
Keywords: Endangered species -- Geographical distribution -- Maps; Endangered ecosystems -- Geographical distribution -- Maps